A legal perspective of the development of strata management in Peninsular Malaysia: A review of the Strata Title Act 1985 - Mohamad, Mazliza; Sufian, Azlinor; Mohamad, Nor Asiah (2011)
The strong growth of economy in Malaysia over the last 20 years has led to the increase in urbanization resulting to changes in the property development generally. With the scarcity of land and changes of living lifestyle, property developers are being more innovative in their developments. This development has tremendously changed from horizontal to vertical approach. The problem starts to arise when parcel owners tend to look after their own private unit but neglect the common property which belongs to everybody. Consequently, landscaped areas become unattended, stairways become filthy and the building lack of proper maintenance. The Strata Titles Act 1985 (“STA”) has been introduced to regulate matters related to strata buildings inter alia on the management and maintenance of common properties. The Act has been in existence for nearly 26 years in Malaysia and it has gone through various amendments. One of the fundamental issues which led to those amendments is the maintenance and management of the buildings and common property of strata development. There are numerous complaints on maintenance and management issues involving the developer and parcel owners. Some of the challenges faced by the industry are the time period itself,the eligibility of parcel owners to attend the meeting, the difficulty of fixing an appropriate time for the meeting, reluctance of the parcel owners to attend the meeting or to serve as Council members. This paper will look into the issues and problems confronting multi-storey buildings in Malaysia prior to the newly amended STA and newly enacted Building and Common Property (Maintenance and Management) Act 2007 (Act 663) (“BCPMM Act”). It will further examine the issues and challenges faced by the developer and parcel owners after the implementation of the amended STA and newly enacted BCPMM Act.